2010
DOI: 10.3171/2009.9.jns081670
|View full text |Cite
|
Sign up to set email alerts
|

Association of a younger age with an increased risk of angiographic and symptomatic vasospasms following subarachnoid hemorrhage

Abstract: Results in this study show that a younger age is associated with an increased incidence of angiographic and symptomatic vasospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 49 publications
1
16
2
Order By: Relevance
“…This relatively high rate of angiographic CV is likely due to the high vasoreactivity of the vessels in young individuals. In contrast, as explained by Magge et al, 29 the increased stiffness of the cerebral vasculature associated with advanced age may explain the lower prevalence of angiographic CV in the population of older adults. Postmortem studies in humans have indicated that aging leads to an increased accumulation of collagen in the vessel wall, along with intimal thickening and fibrosis.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…This relatively high rate of angiographic CV is likely due to the high vasoreactivity of the vessels in young individuals. In contrast, as explained by Magge et al, 29 the increased stiffness of the cerebral vasculature associated with advanced age may explain the lower prevalence of angiographic CV in the population of older adults. Postmortem studies in humans have indicated that aging leads to an increased accumulation of collagen in the vessel wall, along with intimal thickening and fibrosis.…”
Section: Discussioncontrasting
confidence: 45%
“…For example, Yoshimoto and Kwak 49 and Macdonald et al, 28 who used DSA to diagnose CV, observed that a younger age is associated with a greater frequency of severe angiographic CV. Magge et al 29 also reported that the likelihood of severe vasospasm was greater with a younger age; patients with severe angiographic CV were on average 9 years younger than those with no CV. Again, this is likely attributable to the relatively increased vasoreactivity at younger ages.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…10 Age, the third main independent factor for the development of DCI, was left out of our grading system. Although age is well described as an independent predictor of outcome and advanced age has been consistently associated with lower incidence of angiographic vasospasm and DCI, 16,[30][31][32][33] aging is inversely related to favorable outcomes. 3 Older age is associated with larger subarachnoid clot volume, 34 and elderly patients (>60 years) have significant increased risk of poor outcome 3 because of higher rates of medical complications, 32,35 the main reason age was not included in our grading scale.…”
Section: 11mentioning
confidence: 99%
“…10) Recent reports of predictors of vasospasm are shown in Table 2. 3,8,10,11,19,22,29,30,34) In addition, studies have used near-infrared spectroscopy, xenon CT, perfusion CT, and probability index, but many of these methods are detectors of vasospasm, not predictors of vasospasm. These reports showed no clear threshold.…”
Section: Discussionmentioning
confidence: 99%